Al Musykilaat Fi Ta’limin Nahwi Bi Madrasah Ar-Rohmah Malang - Radi Suparlan, Muhammad Haddad Richard (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2024)
Abstract This research aims to describe the problems of nahwu learning, which includes learning methods, learning media, inhibiting factors, as well as efforts that can be made to overcome the difficulties faced by class X students at Ar-Rohmah Integral High School, Malang. Data was obtained through observation, interviews, and documentation. This type of research uses descriptive qualitative. The research results show that: (1) The Nahwu learning process for class X of Ar-Rohmah Malang Integral High School uses lecture, question and answer, discussion, and presentation methods. (2) Problems with Nahwu learning in class come from students rather than from learning media and environmental factors. The problems with students are their different educational backgrounds and lack of interest in learning, difficulty finding someone to talk to, and difficulty placing vocabulary according to the rules. The problem with learning media is that it uses simple media. (3) The environmental problem is that mandatory Arabic language needs to be implemented. Students and educators carry out efforts to overcome this problem. The efforts made by students are memorizing Arabic vocabulary and practicing it, as well as using Arabic in the school environment. Efforts created by educators are using interactive learning methods for students, media used using application technology or websites and trying to provide motivation and encouragement to students to speak Arabic in the school environment